Experimental investigation on low-velocity impact response of carbon/glass hybrid S-shaped foldcore sandwich structure. (November 2022) - Deng, Yunfei; Li, Xiang; Hu, Xiaoyu; Wu, Huapeng; Zhou, Chunping; Lu, Pengcheng
Abstract: Hybrid composites offer an effective method of improving toughness and impact properties while reducing the cost of an advanced composite material. This paper aims at experimentally investigating the influences of impact energy, impact position and ply combination on the low-velocity impact responses of carbon/glass hybrid S-shaped foldcore sandwich structures. Carbon/glass hybrid S-shaped foldcore sandwich structures were manufactured using plain weave carbon fabrics and satin weave glass fabrics with epoxy resin. Low-velocity impact tests were carried out to study the impact behavior. The results show that the damage mode of the sandwich panel gradually changed from the local damage of the top face sheet and the foldcore to the complete penetration damage of the sandwich panel with the increase of the impact energy. And the node position has higher load carrying capacity, energy absorption capacity, and resistance to deformation compared with the base position. Although the initial load carrying capacity of carbon/glass hybrid sandwich panels is lower than that of the carbon fiber reinforced plastic (CFRP) sandwich panels, the addition of glass fabrics can improve energy absorption capacity and perforation threshold of CFRP sandwich panels. Highlights: Carbon/glass hybrid S-shaped foldcore sandwich structures were designed. Effect of impact energy, impact location and ply combination on the dynamic response and damage modes was evaluated. Increasing energy absorption of CFRP S-shaped foldcore sandwich structures using hybridization technique.